Political Accidents in Zimbabwe - Fontein, Joost (Kronos: Southern African Histories, 2020)
On 16 August 2011 Zimbabwe awoke to the news that retired General Solomon Mujuru, aka Rex Nhongo (his war alias), the former deputy commander of ZANLA (Zimbabwe African National Liberation Army) and independent Zimbabwe’s first black army commander, husband of the (then) vice-president, Joice Mujuru, longterm confidante of (then) president Robert Mugabe, and widely regarded as ‘kingmaker’ with the Zimbabwe African National Union Patriotic Front (ZANU PF), had died in a mysterious fire at his farm in Beatrice, 60 km south west of Harare. Just four days later, on 20 August, amid public statements of grief from across the political spectrum, and growing speculation about the cause of his death, Mujuru’s remains were buried at the National Heroes Acre in Harare at a huge state funeral attended by tens of thousands of people. After the ‘inexplicable, horrendous fire accident’ – as Mugabe then described it – there was only a ‘small pile of charred bones and ash’ to be buried, and workers reportedly needed ‘shovels to scrape his remains off the floor’. ‘Burnt beyond recognition’, unconfirmed reports suggested dental records were needed to confirm his identity; and (unusually for state funerals in Zimbabwe) the ‘coffin remained sealed’. Nevertheless, the closed casket did little to contain the plethora of rumours that emerged in the months that followed, which remain unresolved, despite police investigations and an official inquest.